Pengaruh Rasio Profitabilitas dan Leverage Terhadap Earnings Per Share (EPS) (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2012-2015) - Nurul Amaliah Zamri; Atiek Sri Purwati; Sudjono Sudjono (Al-Tijary, 2016)
This type of research is quantitative research. This study entitled "Effect of Profitability Ratio and Leverage to Earnings Per Share (EPS) (Empirical Study On Manufacture Company that Listed on Indonesia Stock Exchange 2012 to 2015)". The purpose of this study is to determine the effect of Basic Earning Power and Debt to Equity Ratio to Earnings Per Share. The population in this study were 143 companies listed on the Indonesian Stock Exchange (BEI) during the years 2012-2015. The sampling technique in this study using purposive sampling with total sample of 62 manufacture companies. Methods of data collection using documentation against secondary data collecting and recording data from the manufacture company's financial report 2012-2015 and the data analysis technique used is multiple linear regression analysis. Based on the results of research and analysis by using SPSS 15 for Windows indicate that: (1) Basic Earning Power has significant positive effect on earnings per share, (2) Debt to Equity Ratio hasn’t significant effect on earnings per share. The implications of this research is Basic Earning Power can be improved by managing all assets that owned by the company to increase net sales of the company so as to increase the advantages to be gained by shareholders as Earning Per Share. Companies should be able to utilize of debt funds as one of the funds used to support the company operations such as working capital, purchase of assets and etc. So that debt funds can increase of revenue for the company and this increase will have an impact on profit after tax. The Condition causes earnings per share also  increased.